Acquired Resistance to Ancrod Its Evaluation and Clinical Occurrence - Vinazzer, H (Thrombosis and Haemostasis, 1973)
A simple test for the detection and quantitation of resistance to ancrod is described. The test is based on the polymerization of fibrinogen by ancrod. The possible variables of the method such as the concentration of fibrinogen, the adsorption of ancrod onto a normal serum protein and the kinetics of the reaction between ancrod and the inactivating substance are examined. By this method, in 4 out of 19 patients who had previously received ancrod, resistance could be detected up to 15 months after therapy. In one of those patients, a second series of doses of ancrod was given. When the dose was elevated to an extent corresponding to the concentration of the inactivating substance, hypofibrinogenemia could be promptly established. The clinical importance of the test is discussed.